2013
DOI: 10.1038/ajg.2012.393
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Manifestations of Inflammatory Bowel Disease Differ Between Hispanics and Non-Hispanic Whites: Results of a Large Cohort Study

Abstract: This study demonstrates differences in IBD presentation among NHW, US-born Hispanic, and foreign-born Hispanic groups. Further investigation to identify environmental and genetic differences between ethnic groups affected by IBD is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 17 publications
3
50
0
2
Order By: Relevance
“…The demographics of our study are, therefore, consistent with other recently published papers that have examined ethnic differences in the IBD patient population in North America [5][6][7]. A statistically significant difference was found in the age of diagnosis of Haitians and Cape Verdeans.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The demographics of our study are, therefore, consistent with other recently published papers that have examined ethnic differences in the IBD patient population in North America [5][6][7]. A statistically significant difference was found in the age of diagnosis of Haitians and Cape Verdeans.…”
Section: Discussionsupporting
confidence: 90%
“…In general, the disease appears to be milder in these populations. The global incidence of IBD continues to rise [4], and various studies have demonstrated unique manifestations of disease that are related to ethnicity [5][6][7][8][9]11,[17][18][19]. Further studies, both in the United States and abroad, are needed to form more definite conclusions regarding IBD manifestations in individuals of Haitian and Cape Verdean descent.…”
Section: Time To First Hospitalization (Years)mentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, Hispanic patients are less likely to receive therapy with biologics and immunomodulators when compared to white patients. 6 …”
Section: Introductionmentioning
confidence: 99%
“…Compared with African Americans, greater proportion of Hispanics and Asians were diagnosed with ulcerative colitis than with Crohn's (26). Marked phenotypic racial differences were revealed also in anatomic location of IBD expression.…”
Section: Infl Ammatory Bowel Disease and Colorectal Cancermentioning
confidence: 87%